Adolescent brain development and depression: A case for the importance of connectivity of the anterior cingulate cortex. (November 2016) - Lichenstein, Sarah D.; Verstynen, Timothy; Forbes, Erika E.
Highlights: Anterior cingulate cortex (ACC) is key to adolescent developmental psychopathology. A meta-analysis shows linear adolescent development of ACC-relevant tracts. ACC functional connectivity increases to default mode and salience networks. ACC connectivity is disrupted in adolescent depression. Abstract: We propose that structural and functional connectivity of the anterior cingulate cortex (ACC) represents a critical component of adolescent developmental psychopathology. We hypothesize that connectivity of the ACC, a hub for integrating cognitive, affective, and social information to guide self-regulation across domains, supports adaptive development of self-regulation during adolescence and that, conversely, disrupted maturation of ACC connectivity contributes to the development of depression. To integrate findings on typical development, we report results of a meta-analysis of diffusion imaging findings of typical adolescent development of the cingulum and anterior thalamic radiations, the tracts most relevant to ACC connectivity, and provide a critical review of the literature on ACC functional connectivity. Finally, we review the evidence for altered structural and functional connectivity in adolescents with depression. Although the evidence for our claim is persuasive, a more comprehensive understanding of the ACC's role depends upon future investigations with sophisticated modeling of networks, prospective and longitudinal designs, and examination of structure-function associations.